السمات اللغوية والنحوية لقراءة أبي القاسم الضحاك - Naji, F. F.; Zainal, H.; Ahmad, M. (Universiti Sains Islam Malaysia, 2024)
This study addresses the life of Abu al-Qasim al-Dahhak , the definition of irregular readings and the linguistic and syntactic signs in the signs in the reading of Abu al-Qasim al-Dahhak through explanation and analysis. The choice of Abu al-Qasim al-Dahhak in specific is because it is found that some of researchs are concentrated on some of the Seven Readings such as the readings of Ibnu Kathir, 'Ibn 'Amir, Hamzah and so on. Thus, this study comes to knock the door of the Seven Readings and choose the reading of Abu al-Qasim al-Dahhak as a sample for the study because there is lack of research on him. Perhaps the significance of this topic lies in the fact that the study of the disipline of the readings is benificial because it covers the noblest evidence which is the Quran. Through this study, the focus is given on the linguistic and syntactic signs that are the characteristics of the reading of Abu al-Qasim al-Dahhak which displays the eloquence of Arabic language in which the Quran was revealed. This study relies on inductive approach by collecting all readings of Abu al-Qasim al-Dahhak and dividing them into linguistic and syntactic orientation. Of the most conspicuous research outcomes are that the works on biographies do not satisfy the right of Abu al-Qasim al-Dahhak, and what is written about him is tentatively little, and that these irregular readings possess significant part and effect in the linguistic, syntactic and morphological domains of the Arabic language that contributes to the reinforcement of the Arabic language. It is recommended in this study that Islamic universities should be attentive in teaching the readings of the Quran and spreading the value of this great discipline by making it part of the curriculum.